2021
DOI: 10.1038/s41419-021-03895-2
|View full text |Cite
|
Sign up to set email alerts
|

H2A.Z acetylation by lincZNF337-AS1 via KAT5 implicated in the transcriptional misregulation in cancer signaling pathway in hepatocellular carcinoma

Abstract: In eukaryotes, histones and their variants are essential for chromatin structure and function; both play important roles in the regulation of gene transcription, as well as the development of tumors. We aimed to explore the genomics data of hepatocellular carcinoma (HCC), combined with literature analysis, in terms of the histone variant H2A.Z. Cell phenotype assay confirmed the effect of H2A.Z on the proliferation, metastasis, apoptosis, and cell cycle of HCC cells. H2A.Z was shown to function via the tumor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The cellular levels and biological activities of these enzymes provide a direct link between epigenetic modifications and the control of cancer signaling, transcription, and cell growth. Furthermore, acetylation of histone variant H2A.Z is also implicated in the transcriptional misregulation in cancer signaling pathway in HCC ( Yuan et al, 2021 ). Aberrant regulation by acetylation on these signaling pathways and biological processes resulted in carcinogenesis and progression of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…The cellular levels and biological activities of these enzymes provide a direct link between epigenetic modifications and the control of cancer signaling, transcription, and cell growth. Furthermore, acetylation of histone variant H2A.Z is also implicated in the transcriptional misregulation in cancer signaling pathway in HCC ( Yuan et al, 2021 ). Aberrant regulation by acetylation on these signaling pathways and biological processes resulted in carcinogenesis and progression of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies in some preclinical models have indicated that epigenetic modulators participate in the regulation of immune response, suggesting that targeting epigenetic process is a rationale strategy for cancer therapy [ 29 31 ]. Recent studies have found that z-acetylation of KAT5 is associated with transcriptional misregulation of tumor signaling pathways in hepatocellular carcinoma, suggesting that KAT5 may be involved in the pathogenesis of hepatocellular carcinoma [ 32 ]. We discovered decreased level of KAT5 in liver cancer cells after abrine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hyuk Moon found that MAPK is frequently activated in liver cancer, which follows by a number of genetic mutations in Hepatocellular cancer cells 26 . The study by Yin Yuan et al found that lincZNF337 can acetylate the H2A via KAT5 to further transcriptionally misregulate the cancer signaling pathway in liver cancer 27 .…”
Section: Discussionmentioning
confidence: 99%